Gestational and childhood exposure to per- and polyfluoroalkyl substances and cardiometabolic risk at age 12 years. (February 2021) - Li, Nan; Liu, Yun; Papandonatos, George D.; Calafat, Antonia M.; Eaton, Charles B.; Kelsey, Karl T.; Cecil, Kim M.; Kalkwarf, Heidi J.; Yolton, Kimberly; Lanphear, Bruce P.; Chen, Aimin; Braun, Joseph M.
Highlights: Gestational PFOA exposure was associated with unfavorable cardiometabolic risk. Gestational PFHxS exposure was associated with unfavorable cardiometabolic risk. A novel risk score was used to assess adolescents' cardiometabolic risk. Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) may adversely influence cardiometabolic risk. However, few studies have examined if the timing of early life PFAS exposure modifies their relation to cardiometabolic risk. We examined the influence of gestational and childhood PFAS exposure on adolescents' cardiometabolic risk. Methods: We quantified concentrations of four PFAS (perfluorooctanoate [PFOA], perfluorooctane sulfonate [PFOS], perfluorononanoate [PFNA], and perfluorohexane sulfonate [PFHxS]) in sera collected during pregnancy, at birth, and at ages 3, 8, and 12 years from 221 mother–child pairs in the HOME Study (enrolled 2003–06, Cincinnati, Ohio). We measured cardiometabolic risk factors using physical examinations, fasting serum biomarkers, and dual-energy X-ray absorptiometry scans at age 12 years. Cardiometabolic risk summary scores were calculated by summing age- and sex-standardized z-scores for individual cardiometabolic risk factors. We used multiple informant models to estimate covariate-adjusted associations of serum PFAS concentrations (log2 -transformed) at each visit with cardiometabolic risk scores and their individual components, and tested for differences in associations across visits. Results: The associations of serum PFOA concentrations with cardiometabolic risk scores differed across visits (P for heterogeneity = 0.03). Gestational and cord serum PFOA concentrations were positively associated with cardiometabolic risk scores (βs and 95% confidence intervals [95% CIs]: gestational 0.8 [0.0, 1.6]; cord 0.9 [-0.1, 1.9] per interquartile range increase). These positive associations were primarily driven by homeostatic model assessment for insulin resistance index (β = 0.3 [0.1, 0.5]) and adiponectin to leptin ratio (β = -0.5 [-1.0, 0.0]). Other individual cardiometabolic risk factors associated with gestational PFOA included insulin and waist circumference. Gestational and cord PFHxS were also associated with higher cardiometabolic risk scores (βs: gestational 0.9 [0.2, 1.6]; cord 0.9 [0.1, 1.7]). Conclusion: In this cohort of children with higher gestational PFOA exposure, fetal exposure to PFOA and PFHxS was associated with unfavorable cardiometabolic risk in adolescence.